Impact of anxiety and stress on the readiness among students after new student orientation programs - Nur Fitri Afriani; Devita Elsanti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: The transition from one school to another marks a critical phase in a student’s educational journey. The transition from elementary school to high school can be challenging as it is a significant milestone in adolescent development. During this period, students experience a variety of physical, emotional, and social changes along with new environments, friendships, and increased academic demands. This can also lead to anxiety and stress in adolescents. Anxiety and stress are mental health conditions that can negatively impact a person's emotional, cognitive, and social functioning. A 2022 study by the Indonesian Adolescent Mental Health Survey found that anxiety disorders are the most common mental health problem among adolescents, affecting 3.7% of the population. Purpose: To determine the impact of anxiety and stress on the readiness among students after new student orientation programs. Method: This study used a quantitative descriptive design with a cross-sectional approach. The study was conducted from July to October at Telkom junior high school, Purwokerto. The population of the study was 210 seventh grade students, but the sample was selected using simple random sampling so that the sample used was 114 respondents. The sample inclusion criteria included students who participated in the school environment introduction program, had a mobile phone, and were in good physical health, while the exclusion criteria were students in grades VIII and IX and students who did not participate in the school environment introduction program. The independent variables in this study are anxiety and stress, while the dependent variable is the school readiness of respondents after the school environment introduction program.The research instrument used was the DASS 42 questionnaire consisting of 28 items to measure the level of anxiety and stress experienced by respondents.. Results: The average age of respondents was 12.219 years with a standard deviation of 0.475 in the age range of 11-13 years as many as 83 respondents (72.8%) and the majority were male as many as 70 respondents (61.4%). the Spearman correlation coefficient of -0.516 with a significance value (Sig. 2-tailed) of 0.000, this indicates a significant negative correlation between anxiety levels and students' readiness to go to school. Conversely, the Spearman correlation coefficient for stress levels with students' readiness to go to school after the school environment introduction activity is -0.996 with a significance value (Sig. 2-tailed) of 0.000, this also indicates a significant negative correlation between stress and school readiness. Conclusion: There is a strong negative correlation between anxiety and stress levels and students' readiness for school after being introduced to the school environment. This suggests that lower stress levels are associated with higher readiness for school. Conversely, higher stress levels are associated with lower readiness for school.